Safety, Tolerability, and Efficacy of Azilsartan Medoxomil With or Without Chlorthalidone During and After 8 Months of Treatment for Hypertension. Issue 3 (24th January 2015) - Kipnes, Mark S.; Handley, Alison; Lloyd, Eric; Barger, Bruce; Roberts, Andrew
<x xml:space="preserve">Abstract</x> A phase 3, 26‐week, open‐label, titrate‐to‐target study (n=418) assessed the safety of azilsartan medoxomil (AZL‐M) alone and with chlorthalidone (CLD), followed by a 6‐week, double‐blind, placebo‐controlled reversal phase with change in clinic diastolic blood pressure (DBP) as the primary endpoint. Target blood pressure (BP) was <140/90 mm Hg (<130/80 mm Hg with diabetes/chronic kidney disease). AZL‐M was initiated at 40 mg once a day (QD), force‐titrated to 80 mg at week 4. CLD 25 mg QD could be added (weeks 8–22), if required, to reach target, followed by additional antihypertensives from week 12. At the end of the open‐label phase, mean change in systolic BP (SBP)/DBP from baseline was −23/−16 mm Hg. The most common adverse events, irrespective of treatment, were dizziness (8.9%) and headache (7.2%). Serious AEs were reported in eight patients (1.9%). Consecutive creatinine elevations ≥50% with values exceeding the upper limit of normal (ULN) were reported in nine (2.2%) patients. All returned to below the 50% threshold; most also returned to below the ULN after drug discontinuation. Mean DBP was maintained through the reversal phase in patients receiving AZL‐M, but increased with placebo (difference: −7.8 mm Hg, 95% confidence interval, −9.8 to −5.8; P<.001). AZL‐M alone or with CLD showed good long‐term safety and stable BP improvements in a titrate‐to‐target approach. BP improvements caused by AZL‐M therapy were safely reversible upon AZL‐M withdrawal.